Impacted Canines Localization and Its Impact on Dental Arch in Orthodontic Patients: A Novel CBCT Clinical Study: Life Sciences -Orthodontics - Alfarra, Yahya H. Y.; Noorani, Tahir Yusuf; Asif, Jawaad Ahmed; Wan Ahmad, Wan Muhamad Amir; Ahmad Rajion, Zainul (International Journal of Life Science and Pharma Research, 2023)
Although impacted canines concerning dental arch have been analyzed in prior studies. However, there is a lack of evidence to analyze the impact of impacted canines on dental arch characteristics using cone beam computed tomography (CBCT) models; therefore, knowing the impact of impacted canines on the dental arch can enhance awareness, contribute knowledge, and aid clinicians in managing impacted canine cases. Hence, it is critical to emphasize the strategies of proper diagnosis and interception for this clinical condition prior to any orthosurgical treatment procedures. This study aimed to analyze the impact of impacted canines on dental arch characteristics in orthodontic patients using CBCT. The method used was the review of clinical records of 350 patients with impacted canines who had CBCT scans and visited the dental clinics for orthodontic treatment pertaining to their arch by dividing them into a control group and a study group. The results revealed a significant relationship based on the dental arch dimension; inter first premolar width (IPW) (P = 0.012), inter first molar width (IMW) (P = 0.010), arch length (AL) (P = 0.041), palatal height (PH) (P = 0.019), and palatal height index (PHI) (P = 0.020). The article concludes that patients with impacted canines had significant changes in dental arch dimension compared to the control group. Dental arch dimensions were significantly deficient, with a higher palatal vault seen in impacted canine patients. The anatomical position of impacted canines has an effect on the dental arches and adjacent anatomical structures. These three-dimensional (3D) findings may provide clinical reference data for impacted canines and provide a valuable basis for delivering information and education on impacted canines assessment and treatment. CPD/Clinical Relevance: Canine impactions are common during routine examinations. Understanding the influence of impacted canines on the dental arch will help clinicians manage impacted canine patients.